2012
DOI: 10.2147/ijn.s29147
|View full text |Cite
|
Sign up to set email alerts
|

In vivo tumor targeting of gold nanoparticles: effect of particle type and dosing strategy

Abstract: Gold nanoparticles (GNPs) have gained significant interest as nanovectors for combined imaging and photothermal therapy of tumors. Delivered systemically, GNPs preferentially accumulate at the tumor site via the enhanced permeability and retention effect, and when irradiated with near infrared light, produce sufficient heat to treat tumor tissue. The efficacy of this process strongly depends on the targeting ability of the GNPs, which is a function of the particle's geometric properties (eg, size) and dosing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 30 publications
3
60
0
Order By: Relevance
“…This assumption is confirmed by the data of Ref. [24], where it was shown that the maximal accumulation of nanorods in the tumour is observed in the case of triple injection of nanoparticles.…”
Section: Resultssupporting
confidence: 81%
“…This assumption is confirmed by the data of Ref. [24], where it was shown that the maximal accumulation of nanorods in the tumour is observed in the case of triple injection of nanoparticles.…”
Section: Resultssupporting
confidence: 81%
“…Au nanoparticles with their unique size dependent properties have been used in a variety of applications that include catalytic agents, biosensors, pharmaceuticals, imaging, and electronics [125][126][127][128][129][130]. Because of their unique properties and applications, research has focused on using alternative methods for manufacturing Au nanoparticles.…”
Section: Gold (Au)mentioning
confidence: 99%
“…7,27,29 In order to decrease toxicity, one of the most effective options is to decrease the size of the nanoparticles, making them behave as supermolecules which can induce "leakage" of nanoparticles in vivo mediated by the kidney. 30, 31 Choi et al proposed that nanoparticles can be cleared when the hydrodynamic size of nanoparticles is decreased to 5.5 nm. 32 We can define this hydrodynamic size as the size of the renal clearance barrier (Figure 1).…”
Section: Dear Editormentioning
confidence: 99%